Endometritis treatment with a PGF2a analog does not improve reproductive performance in a large dairy herd in Argentina - Mejia, Miguel Eduardo (2005)
In Argentina, most dairy cows with endometritis are treated with prostaglandin (PGF2α or its analogs) and insemination is withheld until there are no signs of endometritis. The objective of the present study was to evaluate if this method of managing endometritis enhances reproductive performance. Three experiments were conducted over 4 years in a large farm in the west of Buenos Aires province. In Experiment 1, half of the cows diagnosed with endometritis (>1.5-fold difference in diameter of uterine horns, as determined by rectal palpation) received standard endometritis management (treatment with tiaprost, a PGF2α analog, rectal palpation every 20 days, and withholding of AI until endometritis apparently resolved) and the other half was untreated, with AI at the first estrus after the voluntary waiting period. Untreated cows were inseminated and conceived 20 days earlier than treated cows, and the pregnancy rate by Day 90 postpartum was higher in the untreated group. In Experiment 2, cows with endometritis were divided into four groups according to the severity of symptoms; within each group, cows were allocated to treatment or control, as in Experiment 1. Although first service conception rate decreased as endometritis severity increased, reproductive performance in treated versus control cows was similar to that of Experiment 1 (with no interaction due to degree of endometritis). Re-evaluation of the treated cow (to confirm uterine “normality”) may have been responsible for the delay in conception in both experiments. The objective of Experiment 3 was to determine the effects of tiaprost treatment on clinically normal postpartum cows (no evidence of endometritis). Tiaprost treatment reduced the interval from calving to conception in multiparous cows, but it delayed conception and reduced the conception rate in primiparous cows. In conclusion, treatment with tiaprost impaired reproductive performance in primiparous cows (in the absence of endometritis). Furthermore, the standard treatment for endometritis (treatment with a prostaglandin analog and withholding insemination until clinical signs abated) impaired reproductive performance and increased costs.